Cultivating the savanna: implications of land use change for Maasai livelihoods and wildlife conservation in East Africa - Lynn, Stacy J., author; Coughenour, Michael B., advisor; Galvin, Kathleen A., 1949-, committee member; Theobald, David M., committee member; Fernandez-Gimenez, Maria Edith, committee member; Swift, David M. (David Munson), committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Department Head: N. LeRoy Poff.
Keywords: wildlife conservation; Tanzania; livelihoods; landscape ecology; land use; cultivation; Savanna ecology -- Africa, East; Wildlife conservation -- Africa, East; Maasai (African people); Land use -- Africa, East